Pengaruh Total Assets Turnover, Debt to Equity Ratio dan Return on Equity terhadap Harga Saham pada PT Aneka Tambang Tbk yang Terdaftar di Bursa Efek Indonesia Periode 2015-2024 - Denisa Fitriya 'Uzzahra; Furtasan Ali Yusuf; Kenedi Kenedi (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
The study was designed with the aim of determining the effect of TATO, DER, and ROE variables on stock price variables. A quantitative approach was used in this study, with time series data analysis through a multiple linear regression model based on Ordinary Least Squares (OLS), which was processed using Eviews12 software. The partial results of the TATO variable obtained While the DER variable showed meaning that acceptance of and ROE obtained a stating that was accepted. The results of the study simultaneously showed a In conclusion, TATO, DER, and ROE simultaneously and significantly influence stock price movements. However, TATO was found to have no significant effect on stock prices. In contrast, DER and ROE showed a significant real impact on stock prices.